Functional Identification of the Xanthomonas oryzae pv. oryzae Type I-C CRISPR-Cas System and Its Potential in Gene Editing Application - Liu, Qibing; Wang, Siwei; Long, Juying; Chen, Zhuoyue; Yang, Bing; Lin, Fei (Frontiers in Microbiology, 2021)
The type Ⅰ clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas) system is one of five adaptive immune systems and exists widely in bacteria and archaea. In this study, we showed that Xanthomonas oryzae pv. oryzae (Xoo) possesses a functional CRISPR system by engineering constructs mimicking its CRISPR cassette. CRISPR array analysis showed that the TTC at the 5'-end of the target sequence is a functional protospacer-adjacent motif (PAM) of CRISPR. Guide RNA (gRNA) deletion analysis identified a minimum of 27-bp spacer that was required to ensure successful self-target killing in PXO99A strain. Mutants with deletion of individual Cas genes were constructed to analyze the effects of Cas proteins on mature CRISPR RNA (crRNA), processing intermediates and DNA interference. Results showed that depleting each of the three genes, cas5d, csd1 and csd2 inactivated the pre-crRNA processing, whereas inactivation of cas3 impaired in processing pre-crRNA. Furthermore, the Xoo CRISPR/Cas system was functional in Pseudomonas syringae pv. tomato. Collectively, our results would contribute to the functional study of CRISPR/Cas system of Xoo, and also provide a new vision on the use of bacterial endogenous systems as a convenient tool for gene editing.